Examining the mechanisms by which women's status and empowerment affect skilled birth attendant use in Senegal: a structural equation modeling approach - Kyoko Shimamoto; Jessica D. Gipson (BMC, 2017)
Abstract Background Despite the reduction in maternal deaths globally, maternal mortality rates remain unacceptably high, particularly in some regions of the world. In sub-Saharan Africa, maternal mortality rates have even increased recently, with 201,000 deaths in 2015 as compared to 179,000 in 2013. Use of a skilled birth attendant (SBA) at delivery has remained low, despite evidence of the effectiveness of SBAs in reducing maternal deaths. Women's empowerment is increasingly recognized as a key determinant of maternal health care-seeking and outcomes, yet empirical examinations of the linkages between women's empowerment and delivery care use are particularly limited, especially from sub-Saharan Africa. Methods Using data from the 2010 Senegal Demographic and Health Survey (n = 7451), in this study we employed structural equation modeling (SEM) to investigate the complex and multidimensional pathways by which three women's empowerment domains (household decision-making, attitudes towards violence, and sex negotiation) directly and indirectly affect SBA use. Results Although variations were observed across measures, many of the women's status and empowerment measures were positively related to SBA use. Notably, women's education demonstrated a substantial indirect effect: higher education was related to older age at first marriage, which was associated with higher levels of empowerment and SBA use. In addition to age at first marriage, gender-role attitudes (e.g., progressive attitudes towards violence and sex negotiation) were significant mediators in the relationship between education and SBA use. However, household decision-making was not significantly associated with SBA use. Conclusions Findings indicate significant effects of women's education, early marriage, and some dimensions of women's empowerment on SBA use. SEM was particularly useful in examining the complex and multidimensional constructs of women's empowerments and their effects. This study informs policy recommendations and programmatic efforts to reduce maternal mortality in sub-Saharan Africa by strengthening support for women's access to higher education, delaying marriage and childbearing among girls and young women, and supporting more equitable gender norms.